Identity Politics in the Frame of Maqāṣid Syarī`ah: Realizing Just and Civilized Pluralism in Indonesia - Hasibuan, Indah Malini (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Identity politics is a growing phenomenon in democratic countries, particularly within multicultural societies such as Indonesia. On one hand, identity politics may serve as a medium for minority groups to gain recognition and assert their identity. On the other hand, it may be utilized as a tool to influence the public to gain political support in the name of religion, race, ethnicity, or particular social groups. This paper aims to examine identity politics through the lens of maqāṣid syarī`ah as an effort to realize a just and civilized form of pluralism. Maqāṣid syarī`ah, as a fundamental principle or objective of Islamic law, aligns with the diverse reality of Indonesian society, both religiously and culturally, by emphasizing the protection of religion, life, intellect, lineage, and property. This research employs a qualitative descriptive method, grounded in a literature review, utilizing an approach that involves collecting various written sources. Primary data include Law Number 7 of 2017 concerning General Elections and General Election Commission Regulation Number 13 of 2024 concerning Election Campaigns for Governors, Regents, and Mayors. Secondary data are obtained from books, articles, journals, verses of the Qur’an, and official documents related to identity politics. The data analysis technique involves examining and interpreting the meanings and relationships between ideas within the texts to provide a comprehensive understanding of the phenomenon of identity politics. The research findings indicate that identity politics can have negative consequences when elements such as religion, ethnicity, race, and culture are deliberately used to marginalize other groups in political competition. Such practices risk undermining national values rooted in Pancasila, potentially weakening social solidarity and leading to societal fragmentation. Maqāṣid syarī`ah provides a constructive framework for promoting justice and civility amidst differences, particularly by emphasizing the preservation and protection of religion, life, and intellect. Through this perspective, all identities can be valued, respected, and approached with unity and tolerance.